RITUAL MAGI DI PADEPOKAN TJIMANDE TARI KOLOT KEBON DJERUK HILIR (TTKKDH) PONTANG DI DESA KESABILAN - Yanwar Pribadi, dkk (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2018)
Indonesian society is famous as religious society, which is wealthy about religiousness value more than confronted with culture combination with religion. From this matter, futhermore research held to investigate society phenomenon particular in Banten region which is still thick in the mystical and magi science as soon as many people look at Banten as central practical magi science. Many variation magi science most found on and practicable by magi specialist in the Banten. This research on focus to magi phenomenon in the Persilatan Jtimande in the region Banten beach, Pontang. This research process to do with observation method reside magi ritual with cast about a proof along with inquiry data although field collecting. In this research will we can find out Banten history in the mystical and magi science at mentioned padepokan. This matter not loose from physical a proof when enter a field of study and must have historical base in the reference type as base reference.